The reliability and validity of a video-based method for assessing hamstring strength in football players - Lee, J. W. Y.; Li, C.; Yung, P. S. H.; Chan, K.-M. (Journal of Exercise Science & Fitness, 2017)
Background/Objective: Evaluating hamstring strength by isokinetic dynamometry is limited by various practical issues such as time and cost. A video-based Nordic hamstring exercise is introduced as an alternative option. The aims of this study are to evaluate 1.) the between-session reliability and 2.) concurrent validity of the testing method compared to a standardized isokinetic dynamometry. Methods: Thirty male elite footballers were recruited for the study. From the Nordic hamstring exercise, the video-analysis-determined Nordic break-point angles where the participant could no longer withstand the force of the fall (eccentric mode) and the number of seconds that the player could hold at 30° forward flexion angle (isometric mode) were measured. Intra-class correlation coefficients for between-session reliability, Pearson r correlations between the current method and isokinetic dynamometry were calculated. Results: The reliability of the eccentric mode was moderate (ICC (2,1) = 0.82) while that of isometric mode was poor (ICC (2,1) = 0.57). The Nordic break-point angle of the eccentric mode significantly correlated with the concentric and eccentric hamstring peak torque (r = 0.48 and 0.58, p < 0.001), while the isometric was not (r = 0.02 - 0.07, p > 0.05). Conclusion: The eccentric mode of the video-based hamstring strength test was a moderately reliable and valid method to measure the eccentric hamstring strength in elite football players